Peningkatan Kapasitas Produksi Unit Usaha Di Rumah Amal Mis Hubbullah Kelurahan Tangkerang Timur Kecamatan Tenayan Raya Kota Pekanbaru - Silvia Reni Yenti; Amun Amri; Ahmad Fadli; Zultiniar Zultiniar; Sunarno Sunarno; Wisrayetti Wisrayetti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Increasing the production capacity of the business unit at the Mis Hubbullah charity house to develop and improve the business unit so that it is expected to increase income that supports the Education program at the Mis Hubbullah charity house, one of the sources of animal protein that is widely consumed by the public, easy to obtain is fish and the price is cheap, but Fish quickly undergo a process of decay, so it is necessary to preserve fish. Preservation of fish aims to reduce the water content in the fish body so that it does not provide an opportunity for bacteria to breed. Fish undergo the process of decay quickly compared to other foodstuffs. To increase sales value and income, it is necessary to give a touch of innovation so that it can add business units and attract public interest. Therefore, in this community service activity, counseling was carried out on the diversification of processed catfish meat products into practical and more quality catfish nugget products. In addition, training on making catfish nuggets was conducted. Potential targets who will be given counseling are students from the Al-Ansar Mis Hubbullah Foundation.